Exploring Quality-driven Object-oriented Materializations for Software Architectures - Pace, J. Andrés Díaz; Diez, Alejandra C.; Campo, Marcelo R. Falcone (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2004)
Design activities are critical in the development of quality software. Along this line, architecture-based design has been regarded as the right context for analyzing system-wide quality attributes and making principled design decisions therein. However, the materialization of architectural models into object-oriented structures where the decisions made at the architectural level can be reflected and implemented has not been satisfactory bridged yet. One of the reasons for this problem is that, given an architectural model and a set of quality drivers, there exist usually multiple different ways of mapping this input to object-oriented terms. Furthermore, the whole process involves considerable design background and experience. In this context, this paper describes a tool approach, called ArchMatE, to assist developers in the exploration of materialization alternatives.